Applying Learning Analytics to Explore the Effects of Motivation on Online Students' Reading Behavioral Patterns - Sun, Jerry Chih-Yuan; Lin, Che-Tsun; Chou, Chien (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
This study aims to apply a sequential analysis to explore the effect of learning motivation on online reading behavioral patterns. The study’s participants consisted of 160 graduate students who were classified into three group types:  low reading duration with low motivation, low reading duration with high motivation, and high reading duration based on a second-order cluster analysis. After performing a sequential analysis, this study reveals that highly motivated students exhibited a relatively serious reading pattern in a multi-tasking learning environment, and that online reading duration was a significant indicator of motivation in taking an online course. Finally, recommendations were provided to instructors and researchers based on the results of the study.